PENERAPAN COOPERATIVE LEARNING STAD DALAM PENINGKATAN KOMUNIKASI LISAN DAN LITERASI MEMBACA SISWA KELAS V DI SD XYZ TANGERANG : STUDI KOMPARATIF - Patricius Dwi Krisdianto; Hananto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This comparative study aims to examine the effectiveness of the Cooperative Learningmethod—specifically the Student Teams Achievement Division (STAD)—in improvingfifth-grade students’ oral communication and reading literacy skills at SD XYZ Tangerang.The study was motivated by field findings that showed many students had difficultiesexpressing ideas verbally and understanding texts. A quantitative approach with a quasi-experimental design was used, involving two classes: an experimental class using theSTAD model and a control class using conventional lecture methods. Instrumentsincluded a reading literacy test (25 items) and an observation sheet for oralcommunication skills. Data were collected through pretests and posttests, then analyzeddescriptively and inferentially. The results showed that the experimental class experiencedsignificantly greater improvement than the control class. The average reading literacyscore increased from 22.28 to 23.41, with a t-test significance value of 0.002. Oralcommunication skills in the experimental class improved by 3.53 points, while the controlclass only improved by 0.3 points. These findings confirm that the STAD model is moreeffective than conventional methods in improving students’ communication and readingskills. This research provides valuable recommendations for teachers to apply cooperativelearning strategies in classrooms.